Shaping pleasure, shifting boundaries: a roundtable on the future of porn studies - Alilunas, Peter; Florencio, Joao; Jones, Angela; Paasonen, Susanna (United Kingdom, 2025)
The roundtable, ‘Shaping Pleasure, Shifting Boundaries: A Roundtable on the Future of Porn Studies,’ took place in June 2024 via Zoom and was recorded, transcribed and then edited to cut digressions and repetitions for publication. The roundtable was intended to examine the transformative trajectory of porn studies over the last decade. With a focus on technological innovations, ethical challenges, and the labour dynamics reshaping the field, the following discussion explores how intersectionality and diverse methodologies have broadened perspectives within porn studies. Our participants also talked about the rise of platforms like OnlyFans, the impact of archival gaps, and the continuing critical tension between pleasure and danger in academic and cultural narratives. Their conversation underscores the necessity of rethinking traditional paradigms while advocating for inclusivity and the preservation of pornographic histories as part of broader cultural heritage. This conversation sets the stage for envisioning the discipline's future as it navigates a rapidly evolving sociopolitical and technological landscape.